The effects of white matter hyperintensities on MEG power spectra in population with mild cognitive impairment - Torres-Simon, Lucia; Cuesta, Pablo; del Cerro-Leon, Alberto; Chino, Brenda; Orozco, Lucia H.; Marsh, Elisabeth B.; Gil, Pedro; Maestu, Fernando (Frontiers in Human Neuroscience, 2023)
Cerebrovascular disease is responsible for up to 20% of cases of dementia worldwide, but also it is a major comorbid contributor to the progression of other neurodegenerative diseases, like Alzheimer’s disease. White matter hyperintensities (WMH) are the most prevalent imaging marker on cerebrovascular disease. The presence and progression of WMH in the brain have been associated to general cognitive impairment and the risk to develop all types of dementia. The aim of this piece of work is the assessment of brain functional differences in an MCI population based on the WMH volume. 129 individuals with mild cognitive impairment (MCI) underwent a neuropsychological evaluation, MRI assessment (T1 and Flair), and MEG recordings (five minutes of eyes closed resting state). Those participants were further classified into vascular MCI (vMCI) (n = 61, mean age 75 ± 4 years, 35 females) or non-vascular MCI (nvMCI) (n = 56, mean age 72 ± 5 years, 36 females) according to their WMH total volume, assessed with an automatic detection toolbox, LST (SPM12). We used a completely data-driven approach to evaluate the differences in the power spectra between the groups. Interestingly, three clusters emerged: One cluster with widespread larger theta power and two clusters located in both temporal regions with smaller beta power for vMCI compared to nvMCI. Those power signatures were also associated with cognitive performance and hippocampal volume. Early identification and classification of dementia pathogenesis is a crucially important goal for the search for more effective management approaches. These findings could help to understand and try to palliate the contribution of WMH to particular symptoms in mixed dementias progress.